1992
DOI: 10.4319/lo.1992.37.7.1550
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term alteration of in situ currents on the growth of Mercenaria mercenaria in the northern Gulf of Mexico

Abstract: Water currents were experimentally manipulated for 3 months in a shallow subtidal sandflat through a series of nine channels with diverging, parallel, or converging walls (7 m long, 1.2 m high). Three treatments were chosen to bracket the ambient flow rates; vertically averaged velocities were reduced by 40%, reduced by 2%, or increased by 65%. Within the center of each channel, six Mercenaria mercenaria [shell length, 36.9±2.2 mm (mean ± 1 SD)] were placed haphazardly in 0.25‐m2 plots. Although water‐column c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Thus, the traditional method of collecting water samples by matching the collection speed to the ambient current (i.e. isokinetic sampling) will likely produce higher estimates of the food level available than that lect data on the variability in food we chose sources and water currents were measured above the bare sand (A) (Judge et al 1992). Sampling of food resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the traditional method of collecting water samples by matching the collection speed to the ambient current (i.e. isokinetic sampling) will likely produce higher estimates of the food level available than that lect data on the variability in food we chose sources and water currents were measured above the bare sand (A) (Judge et al 1992). Sampling of food resources.…”
Section: Introductionmentioning
confidence: 99%
“…Data was collected bi-monthly for 1 yr and every 4 h over one 24 h period. Samples were taken in habitats similar to those used for several Mercenaria mercenaria growth experiments (Coen & Heck 1991, Wilson 1991, Judge et al 1992. In the bi-monthly program, vertical profiles were sampled at 4 horizontal locations (bare sand, edge of seagrass Halodule wrightii bed, and 2 distances into the seagrass bed) representing different habitat types.…”
Section: Introductionmentioning
confidence: 99%
“…In shallow aquatic habitats, organic matter fluxes are driven by hydrodynamic processes that determine the magnitude of food supply to consumers, depending on its origin and quality. Hydrodynamic factors determine the residence time of resuspended particles in the water column, thereby regulating the response of suspension feeders (Judge et al 1992, Wildish & Kristmanson 1997. Indeed, the flux of particles available to bivalves is a function of both horizontal advection and concentration of food particles in the boundary benthic layer.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective was to generalise on another aspect of the ecological response of filter feeders that were present in different natural hydrodynamic conditions as a priori assumptions (Judge et al 1992). The hypothesis tested was whether 2 different hydrodynamic configurations influenced isotopic origin and biochemical quality of food supply and whether, by means of a transplant experiment, the isotopic patterns of food that was assimilated by bivalves were related to the origin of the food availability as a function of the different hydrodynamic typology.…”
Section: Introductionmentioning
confidence: 99%
“…Wildish and Kristmanson 1984;Frechette et al 1989;Peterson and Black 199 1). Alternatively, Grizzle and Mot-in (1989), Grizzle and Lutz (1989) and Emerson (1990) suggested that elevated horizontal seston flux (rather than seston concentration) is responsible for the positive relationship between growth rate and flow speed for the infaunal bivalves Mercenaria mercenaria and Mya arenaria (but see Cahalan et al 1989;Judge et al 1992 rates with increasing flow speed have also been attributed to the direct inhibitory effects of high flow speed on mechanical aspects of feeding in several bivalve species (Wildish et al 1987(Wildish et al , 1992Eckman et al 1989;Judge et al 1992;Wildish and Saulnier 1992), including the blue mussel Mytihs edulis (Wildish and Miyares 1990). Sampling both near-bed food concentration and currents at the spatial and temporal scales required to directly evaluate the mechanism(s) controlling food supply to the organisms is constantly improving with advances in technology.…”
mentioning
confidence: 99%